Dynamic response of common stone masonry buildings under uncertain material properties - Adhikari, Rabindra; Gotame, Sanjita; Regmi, Puja; Karki, Bipin; Gautam, Dipendra (Journal of Engineering Issues and Solutions, 2023)
The major causes of the failure of the structure are either improper design or improper construction. Therefore, accurate analysis for the design of the structure is of utmost importance. However, it is extremely difficult and impractical to determine all the engineering properties of the building structure and all of its components’ analysis of each building. It is customary to adopt typical values of material properties for the analysis of such structures, usually required for seismic vulnerability analysis. However, there is a high variation in material characteristics, especially of stone masonry that can have a significant effect on the analysis. Typical stone masonry was investigated at the site and then analyzed using finite element model (FEM). Parametric analysis was conducted for a range of young’s modulus of elasticity values of a masonry wall. The dynamic characteristics of the building were determined from the modal analysis. Seismic loading was done using dynamic methods and its effect was determined as design stresses and building deformations for the comparison. The results indicated that various building responses have a different relationship with the elasticity parameter of the wall, indicating that a very good engineering judgment is required in the analysis of stone masonry buildings that do not have standard material properties.